Teaching and learning linear programming in a grade ii multilingual mathematics class of English language learners: exploring the deliberate use of learners home language - Nkambule, Thulisile (My University, 2009)
This study investigated the deliberate use of learners‟ home languages in the teaching and learning of linear programming. The study involved a Grade 11 teacher and his Grade 11 multilingual learners in a township school in the East Rand. Data was collected through lesson observations for five consecutive days, reflective interview with teacher and clinical interview with two learners. Analysis of data revealed that the teacher used learners‟ home languages to probe learners‟ understanding of specific terms frequently used in linear programming concepts, for example terms such as, „at least‟ and „at most‟. Learners‟ responses suggest that they drew on their home languages for the meaning of these words. Learners explained the term „at least‟ in their home languages as „buncinci‟ in Isixhosa, „bonnyane‟ in Sesotho and Sepedi and „okungenani‟ in IsiZulu. Learners also used mathematical English term minimum to explain „at least‟ and maximum to explain „at most‟.
Keywords: Linear programming; learners home language; deliberate; mathematical language; at least and at most; Realistic Mathematics Education; Horizontal mathematization; vertical mathematisation